2018
DOI: 10.1016/j.tcs.2018.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Mutual dimension and random sequences

Abstract: If S and T are infinite sequences over a finite alphabet, then the lower and upper mutual dimensions mdim(S : T ) and M dim(S : T ) are the upper and lower densities of the algorithmic information that is shared by S and T . In this paper we investigate the relationships between mutual dimension and coupled randomness, which is the algorithmic randomness of two sequences R 1 and R 2 with respect to probability measures that may be dependent on one another. For a restricted but interesting class of coupled prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Third, and most crucially, this principle implies that, in order to prove a lower bound dim H (E) ≥ α, it suffices to show that, for every A ⊆ N and every ε > 0, there is a point x ∈ E such that dim A (x) ≥ α − ε. 5 For the (≥) direction of this principle, we construct the minimizing oracle A. The oracle encodes, for a carefully chosen sequence of increasingly refined covers for E, the approximate locations and diameters of all cover elements.…”
Section: From Points To Setsmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, and most crucially, this principle implies that, in order to prove a lower bound dim H (E) ≥ α, it suffices to show that, for every A ⊆ N and every ε > 0, there is a point x ∈ E such that dim A (x) ≥ α − ε. 5 For the (≥) direction of this principle, we construct the minimizing oracle A. The oracle encodes, for a carefully chosen sequence of increasingly refined covers for E, the approximate locations and diameters of all cover elements.…”
Section: From Points To Setsmentioning
confidence: 99%
“…The above-described dimensions dim(x) and Dim(x) of a point x in Euclidean space (or an infinite sequence x over a finite alphabet) are analogous by limit theorems [27,1] to K(u) and hence to H(X). Case and the first author have recently developed and investigated the mutual dimension mdim(x : y) and the dual strong mutual dimension Mdim(x : y), which are densities of the algorithmic information shared by points x and y in Euclidean spaces [4] or sequences x and y over a finite alphabet [5]. These mutual dimensions are analogous to I(u : v) and I(X; Y ).…”
Section: Introductionmentioning
confidence: 99%
“…The first notion of mutual dimension was defined in [3] to analyze the density of algorithmic mutual information between points in Euclidean space. It was then extended to sequences in [4] in order to study coupled randomness. A similar proof can be given for M dim.…”
Section: Definitionmentioning
confidence: 99%
“…In this paper, we discuss several new data processing inequalities for sequences. We use mutual dimension, a recent development in constructive dimension, as the means for measuring the quantity of shared information between two sequences [3,4]. Lutz defined and explored the constructive dimension of sequences in [11], and Mayordomo showed that constructive dimension can be characterized in terms of Kolmogorov complexity in [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation